Avengers, assemble the literature! A multi-study review of consumption, environmental values, and planetary health research - Lim, Weng Marc * (Wiley, 2023)
Mother Earth is dying. Humanity needs to step up. Otherwise, the planet we call home will soon be uninhabitable. The destiny of our planet inarguably depends on consumers, as their choices have the power to turn them into eco-superheroes (sustainable consumption) or eco-villains (unsustainable consumption). This article aims to review the current progress of consumption research and propose strategies to inspire consumers to embrace their inner eco-warrior spirit, fostering sustainable behavior that protects the environment and supports human well-being. To achieve this, this article employs an integrative approach, merging a meta-perspective on theoretical development with a multi-study methodological approach. Harnessing the power of scientometrics, this article delivers meta-insights from a multi-study analysis on consumption trends in relation to environmental values (micro-perspective; Study 1) and planetary health (macro-perspective; Study 2). These findings pave the way for future research and intervention strategies designed to nurture ecological sustainability and unleash the eco-warrior in every consumer.